Microgravity-induced transcriptional reprogramming in embryonic chicken limb bud-derived chondrogenic cultures - Kovács, Patrik; Wang, Zhangzheng; Hajdú, Tibor; Juhász, Krisztián Zoltán; Katona, Éva; Takács, Roland; Vágó, Judit; Zákány, Róza; Póliska, Szilárd; Szentesi, Péter; Csernoch, László; Matta, Csaba (Frontiers in Cell and Developmental Biology, 2026)
IntroductionExtended exposure to microgravity, such as experienced during spaceflight, significantly alters the mechanical environment of skeletal tissues, impacting cartilage development and function. Mechanical unloading disrupts the balance of cellular signaling and extracellular matrix synthesis in cartilage precursor cells, but the molecular consequences and temporal dynamics of these alterations remain incompletely understood.MethodsWe employed simulated microgravity via a random positioning machine (RPM) to investigate stage-specific transcriptomic and phenotypic responses in chondrogenic micromass cultures derived from embryonic chicken (Gallus gallus) limb bud cells. RNA sequencing, bioinformatic pathway analysis, and protein interaction network construction were performed on cultures exposed to microgravity for early (days 0–3), late (days 3–6), and continuous (days 0–6) periods.ResultsContinuous microgravity exposure resulted in robust differential expression of 648 genes (adjusted p-value <0.05, |log2 fold change| > 1), including suppression of canonical chondrogenic markers (SOX9, COL2A1) and upregulation of catabolic enzymes (MMP13, ADAMTS family). The affected key signaling pathways included disrupted TGF-β/BMP balance, Wnt/β-catenin activation, and cytoskeletal remodeling. Early and late exposures showed consistent gene expression trends but fewer statistically significant changes. Notably, adrenergic beta receptor 1 (ADRB1) was consistently upregulated across all time points.DiscussionThese findings demonstrate that simulated microgravity rapidly induces reversible molecular and cellular adaptations related to cartilage homeostasis and mechanotransduction in this chondrogenic model system. The RPM platform offers a powerful tool to dissect chondrogenesis, cartilage biology, and lineage plasticity under mechanical unloading, providing insights with broad relevance to skeletal tissue mechanobiology.